TRADISI LOKAL : RITUAL SOPIK DI TAHANE MAKEAN PULAU HALMAHERA SELATAN - Syahril Muhammad; Rustam Hasim; Jainudin Abdullah (Universitas Hasanuddin, 2022)
This study focuses on three main problems, namely (1) how the history of the